2017
DOI: 10.1007/5584_2017_24
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokines in Psychiatric Disorders in Children and Adolescents: A Review

Abstract: Cytokines are a large group of small proteins which play a significant role in cell signaling and regulate a variety of processes in organisms, including proliferation and differentiation of many cells, mediation in defense reactions and regulation of hematopoiesis. Cytokines can be divided into those with pro- and those with anti-inflammatory properties. In the group of pro-inflammatory cytokines the most important are: IL-1 beta, IL-6, TNF-alpha, and IFN-gamma. Pro-inflammatory cytokines might be involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Some authors have proposed that inflammation and several inflammatory mediators, including acute phase proteins and pro‐inflammatory cytokines, may be considered biomarkers of psychosocial stress (Hänsel, Hong, Cámara, & von Känel, ). Previous research had shown that pro‐inflammatory cytokines, the most important of which are IL‐6, interleukin‐1 beta (IL‐1β), tumor necrosis factor‐alpha (TNF‐α), and interferon‐gamma (IFN‐γ), might be involved in the pathophysiology of many psychiatric conditions and clinical disorders in adults (Miłkowska, Popko, Demkow, & Wolańczyk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have proposed that inflammation and several inflammatory mediators, including acute phase proteins and pro‐inflammatory cytokines, may be considered biomarkers of psychosocial stress (Hänsel, Hong, Cámara, & von Känel, ). Previous research had shown that pro‐inflammatory cytokines, the most important of which are IL‐6, interleukin‐1 beta (IL‐1β), tumor necrosis factor‐alpha (TNF‐α), and interferon‐gamma (IFN‐γ), might be involved in the pathophysiology of many psychiatric conditions and clinical disorders in adults (Miłkowska, Popko, Demkow, & Wolańczyk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as documented in the literature they are implicated in the development of psychiatric comorbidities associated with AN, in particular anxiety, depression, phobic ideation, and obsessive behavior. 10,31,56,57 However, how the cytokines become protagonists of these processes is not yet completely understood and would be worthy of future study and investigation. Since the levels of pro-inflammatory cytokines are related to the severity of the disorder and the response to treatment, they could be considered non-specific markers in the evaluation of these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently little evidence to inform the use of adjunctive anti-inflammatory agents in children and adolescents with psychiatric disorders. Studies of peripheral inflammatory markers in this population have been equivocal, largely limited by similar methodological factors as adult studies (42,43).…”
Section: Need For Pediatric Studies and Early Interventionmentioning
confidence: 99%